Who Gets to Adopt? Contested Values Constrain Just Transitions to Agroforestry - Hastings, Zoe; Wong, Maile; Ticktin, Tamara (Frontiers in Sustainable Food Systems, 2021)
Agroforestry is often promoted as a multi-benefit solution to increasing the resilience of agricultural landscapes. Yet, there are many obstacles to transitioning agricultural production systems to agroforestry. Research on agroforestry transitions often focuses on why farmers and land managers chose to adopt this type of stewardship, with less focus on the political context of practitioner decisions. We use the case study of agroforestry in Hawai‘i to explore how agroforestry transitions occur with particular attention to politics and power dynamics. Specifically, we ask, what factors drive and/or restrain transitions to agroforestry and who is able to participate. We interviewed 38 agroforestry practitioners in Hawai‘i and analyzed the data using constructivist grounded theory. We then held a focus group discussion with interview participants to share results and discuss solutions. Practitioners primarily chose agroforestry intentionally for non-economic and values-based reasons, rather than as a means to production or economic goals. Agroforestry practitioners face a similar suite of structural obstacles as other agricultural producers, including access to land, labor, and capital and ecological obstacles like invasive species and climate change. However, the conflict in values between practitioners and dominant institutions manifests as four additional dimensions of obstacles constraining agroforestry transitions: systems for accessing land, capital, and markets favor short-term production and economic value; Indigenous and local knowledge is not adequately valued; regulatory, funding, and other support institutions are siloed; and not enough appropriate information is accessible. Who is able to practice despite these obstacles is tightly linked with people's ability to access off-site resources that are inequitably distributed. Our case study highlights three key points with important implications for realizing just agroforestry transitions: (1) practitioners transition to agroforestry to restore ecosystems and reclaim sovereignty, not just for the direct benefits; (2) a major constraint to agroforestry transitions is that the term agroforestry is both unifying and exclusionary; (3) structural change is needed for agroforestry transitions to be just. We discuss potential solutions in the context of Hawai‘i and provide transferrable principles and actionable strategies for achieving equity in agroforestry transitions. We also demonstrate a transferrable approach for action-oriented, interdisciplinary research in support of just agroforestry transitions.